2021
DOI: 10.3390/ani11113184
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Meat Quality and Antioxidant Status of Sheep Supplemented with Tannins: A Meta-Analysis

Abstract: The objective of this study was to evaluate the effects of dietary supplementation with tannins (TANs) on productive performance, carcass characteristics, meat quality, oxidative stability, and blood serum antioxidant capacity of sheep through a meta-analysis. Using Scopus, Web of Science, ScienceDirect, and PubMed databases, a systematic search was performed for studies published in scientific journals that investigated the effects of TANs supplementation on the variables of interest. Only studies with weaned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 136 publications
(190 reference statements)
0
12
1
Order By: Relevance
“…Although it has previously been reported that dietary supplementation of tannin-containing plants can increase HCY and CCY [ 11 ], in this study HCW, HCY, CCW, CCY, ELC, ILC, CG, LL, and CI were similar in lambs of the different treatments. Similar responses were previously reported by Orzuna-Orzuna et al [ 5 ] in lambs supplemented with increasing doses (0, 1, 2, and 3 g kg −1 DM for 56 days) of a PA containing flavonoids, essential oils, and alkaloids; and by Lozano-Sánchez et al [ 23 ] in lambs supplemented with a PA (0, 5, 10, and 15 g kg −1 DM for 60 days) containing 12% hydrolyzable tannins.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Although it has previously been reported that dietary supplementation of tannin-containing plants can increase HCY and CCY [ 11 ], in this study HCW, HCY, CCW, CCY, ELC, ILC, CG, LL, and CI were similar in lambs of the different treatments. Similar responses were previously reported by Orzuna-Orzuna et al [ 5 ] in lambs supplemented with increasing doses (0, 1, 2, and 3 g kg −1 DM for 56 days) of a PA containing flavonoids, essential oils, and alkaloids; and by Lozano-Sánchez et al [ 23 ] in lambs supplemented with a PA (0, 5, 10, and 15 g kg −1 DM for 60 days) containing 12% hydrolyzable tannins.…”
Section: Discussioncontrasting
confidence: 52%
“…However, the pH of the meat of lambs assigned to the PA3 treatment was between 5.5 and 5.8, which is considered normal for sheep meat [ 37 ]. In a recent study, Orzuna-Orzuna et al [ 11 ] observed that sheep meat pH decreased in response to dietary supplementation of hydrolyzable tannins. It has been reported that microbial spoilage of sheep meat increases when pH is higher than 5.8 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meta-analysis, the heterogeneity of treatment effect was assessed with the chisquare (Q) test, in which, due to its relatively low power, a significance level of p ≤ 0.10 was used [37]. In addition, the I 2 statistic was used to measure the percentage of variation due to heterogeneity [29]. Negative values of I 2 (percent variation) were assigned as zero, while values less than 25, 25 to 50, and greater than 50% indicated low, moderate, and high heterogeneity, respectively [28,29].…”
Section: Heterogeneity and Publication Biasmentioning
confidence: 99%
“…However, that study [27] only included six references applied to small ruminants in their database and did not evaluate productive performance, blood metabolites, or meat and milk quality. Although the meta-analytical approach has been used mainly in research related to human health, its application in research on natural food additives in domestic animals is still limited [28,29]. MA allows to combine and quantitatively synthesize previously published results from multiple independent studies [30].…”
Section: Introductionmentioning
confidence: 99%